Diversity of cyanobacteria in Sarawak lentic zones - Ramlah, Binti Rahmat. (Universiti Malaysia Sarawak (UNIMAS), 2005)
A study about the diversity of Cyanobacteria is carned out in four locations around Kuching District in Sarawak. They are the Institute of Research center and Fish Production (To r tambroides's ponds) in Tarat; shrimp aquaculture ponds in Lembaga Kemajuan Ikan Malaysia (LKIM), Tasik Semada in Balai Ringin and Tasik Biru in Bau. This study is designed to gain data about the diversity of Cyanobacteria in Sarawak Lentic Zone. From the study conducted, there nine genus of Cyanobacteria have been identified. They were Anabaena, Microcystis, Lyngbya, Oscillatoria, Spintlina, Anacystis, Chaemaesiphonales, Calothrix, and Gleotrichia sp. Among these genera only Gleotrichia, Spintiina, Chaemaesiphonales have no potential to produce toxin during cyanobacterial bloom. The physico-chemical water parameter that been recorded are in the range of I.94mg/l - 1O.32mg/1 for dissolved oxygen (DO), 29°C - 33 °C for temperatu re, and 4.63-9.14 for pH.